Utilization of JWT Tokens as an Authenticity Validation Method for Correspondence at Muhammadiyah University of East Kalimantan - Hendra Saputra; Sayekti Harits Suryawan; Faldi Faldi; Bulan Suci Cahayawati; Ririn Wahyuni (TEPIAN, 2023)
This research aims to evaluate and implement the utilization of JSON Web Token (JWT) to verify the authenticity of letters in the letter system at the University of Muhammadiyah in East Kalimantan (UMKT). The previous method relied solely on QR code signatures, which were susceptible to copying and manipulation, thus posing vulnerabilities in the letter verification process. Therefore, this study used JWT tokens as a more secure and effective verification mechanism. The research involved creating JWT tokens containing important information such as UUID, letter number, subject, content, sender, and recipient. These JWT tokens were inserted into the letters as part of the verification mechanism. The Muhammadiyah University of East Kalimantan letter system was updated to verify JWT tokens by extracting the token from the letter and checking the UUID against the database. The research results demonstrate that utilizing JWT tokens as a method for verifying the authenticity of letters provides advantages in terms of efficiency and accuracy. The letter system, which previously relied solely on QR code signatures, can be enhanced by using JWT tokens. The updated letter system can verify letters' authenticity more reliably and dependably, reducing the risks of manipulation or forgery. The utilization of JWT tokens in the Muhammadiyah University of East Kalimantan letter system offers significant benefits in improving the efficiency of the verification process and enhancing the accuracy of letter identification. In this context, this research provides a safer and more effective solution for ensuring the authenticity of letters, thereby enhancing the security and integrity of the letter management system at Muhammadiyah University of East Kalimantan.